The Strategies for Sustainable Drug Immunization Creation Prevention of the Youths in Bangkok Metropolitan - Kidputtanasombut, Piromsak; Naressenie, Gen.Dr.Kasemchart; Sriharun, Dr.Boonrueng (Journal for Developing the Social and Community, 2018)
The objectives of this research were to propose the appropriate strategies of sustainable. This research was mixed methods of both qualitative and quantitative. The quantitative research was conducted by studying the sample of 205 directors from schools in Bangkok Metropolitan who were selected by stratified random sampling technique and the sample size was obtained by the calculation with Taro Yamane’s formula. The research tool for data collection was a five rating scale questionnaire. The data were analyzed the statistics consisted of percent, mean, standard deviation and the hypothesis were tested by stepwise regression analysis. The qualitative research was conducted by interpretation studying the documents, research, and theory related including interviewing 17 key informants of governmental organizations in Bangkok Metropolitan consisted of Bangkok governor, 10 directors, and 6 district directors who were selected purposively. The data were analyzed using content analysis and interpretation. Strategies were confirmed by focus group discussions conducted with 18 directors from schools who were selected purposively. The research results were as follows: The appropriate strategies for sustainable drug immunization creation and prevention of the youths in Bangkok Metropolitan consisted of 6 approaches : (1) the strategy for creation of knowing and understanding in drug danger and awareness by setting up and developing the learning and entertaining areas for the youth in participative integration form, (2) the strategy for secured society creation by promoting the cooperation in caring, protecting and helping the youths in the form of muti-professional, (3) the strategy for warm family promotion by joining hand with all sectors in organizing various relation activities for the families continuously, (4) the strategy for strengthening the personnel performance by training all personnel for having high cooperation capabilities in utilizing modern innovative information technologies, (5) the strategy for developing the organizational performance by setting up specific commanding center for drug immunization creation and prevention of the youths equipped with drug specialists, devices and modern equipment and (6) the strategy for strong network creation and development by strengthening more incentives to both private and governmental sectors in sustainable drug immunization creation and prevention.